2020
DOI: 10.1021/acs.est.9b05994
|View full text |Cite
|
Sign up to set email alerts
|

Increased Temperature and Turbulence Alter the Effects of Leachates from Tire Particles on Fathead Minnow (Pimephales promelas)

Abstract: Increased temperature and turbulence alter the effects of leachates from tire particles on fathead minnow (Pimephales promelas). Environmental Science & Technology, 54(3), 1750-1759.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 43 publications
6
50
0
Order By: Relevance
“…However, desorption of substances from weathered plastics likely varies for different starting materials, as seen in this study and in previous work with marine copepods which showed simulated weathering (UV) of a variety of plastics resulted in leachates with increased toxicity for some items but unaltered or decreased toxicity for other materials (Bejgarn et al, 2015). Recent lab-based experiments which have begun to explore how certain characteristics of the weathering environment, such as temperature and mechanical stress, can affect leachate toxicity have also indicated that the nature of such changes is complex and product dependent (Kolomijeca et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…However, desorption of substances from weathered plastics likely varies for different starting materials, as seen in this study and in previous work with marine copepods which showed simulated weathering (UV) of a variety of plastics resulted in leachates with increased toxicity for some items but unaltered or decreased toxicity for other materials (Bejgarn et al, 2015). Recent lab-based experiments which have begun to explore how certain characteristics of the weathering environment, such as temperature and mechanical stress, can affect leachate toxicity have also indicated that the nature of such changes is complex and product dependent (Kolomijeca et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
“…While there is now some recognition that plastic pollution may impact marine organisms via leaching of harmful chemicals (Hermabessiere et al, 2017), the effect of weathering on leachate toxicity is still poorly understood. To our knowledge only a few studies have investigated how weathering of plastics affects the toxicity of substances which leach from this material and these have focused on toxicity to eukaryotes rather than to bacteria (Bejgarn et al, 2015;Kedzierski et al, 2018;Gardon et al, 2020;Kolomijeca et al, 2020). In this study, we report that common HDPE and PVC plastic items continue to leach substances following environmental weathering for up to 112-days which can adversely impact Prochlorococcus growth, photosynthesis FIGURE 4 | SYTOX Green stained (i.e., membrane compromised) populations after exposure to different dilutions of weathered HDPE leachates in Prochlorococcus (A-C) MIT9312, (D-F) NATL2A and PVC leachates in Prochlorococcus (G-I) MIT9312, (J-L) NATL2A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent estimates suggest a massive 1 million t/a of tire wear particles enter the environment in the USA, with increasing inputs in recent decades due to mounting vehicle traffic (Wagner et al, 2018). Tire wear particles are the main source of total suspended solids (Göbel et al, 2007), zinc (Councell et al, 2004), and polycyclic aromatic hydrocarbons (PAHs, Boonyatumanond et al, 2007) in urban runoff, and leachate from tires has been linked to acute lethality in coho salmon (Peter et al, 2018) and developmental abnormalities in fathead minnow (Kolomijeca et al, 2020), but has shown milder effects on other organisms (Marwood et al, 2011;Panko et al, 2013;Redondo-Hasselerharm et al, 2018). Since multiple stressors very often underlie "ecological surprises" (non-additive effects e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yet for PAHs, microbes may mitigate negative effects: PAHs generally have negative effects on plants, including duckweed (Becker et al, 2002;Zezulka et al, 2013), but may be rapidly degraded by microbes (Heitkamp and Cerniglia, 1987;Haritash and Kaushik, 2009). While zinc and PAHs are most often expected to drive biological effects, leachate from tires contains a complex mixture of compounds (Peter et al, 2018;Kolomijeca et al, 2020;Capolupo et al, 2020) and main effects on responses of organisms are highly varied (Panko et al, 2013;Peter et al, 2018), precluding clear predictions. However, several studies have found greater effects of leachate at higher temperatures (Marwood et al, 2011;Kolomijeca et al, 2020), so we might predict that warming would exacerbate leachate effects on duckweed, microbes, and their fitness correlations.…”
Section: Introductionmentioning
confidence: 99%